Moral courage of emergency nurses in care-limited environments: A mixed-methods study - Wolf, Lisa Adams (Nursing ethics, 2025)
BackgroundProfessional ethics in nursing exist to guide care and allow for decision-making to be patient-centered. In the current medicolegal landscape post-Roe and in light of bans on gender-affirming care, the decision-making processes of emergency nurses in the clinical environment of care as informed by both professional and personal ethics are an important area of inquiry.AimThe aim of this study was to examine the contribution of moral courage to decision-making by emergency nurses.Research DesignA mixed-methods exploratory sequential approach was used, using a standard demographics form and the Nurses Moral Courage Scale to collect quantitative data. These data were used to inform an interview guide for qualitative data collection. Situational analysis was used to analyze the interview data.Ethical ConsiderationsPrior to recruitment, this study was reviewed and approved by the University of Massachusetts IRB (#00003909). Participants were provided with an informed consent document at the time of registration and at the time of interview; participants provided both signed consent and verbal assent. Participants were assigned study codes to maintain anonymity and data were maintained in a secure University cloud.Participants and Research ContextUS-based emergency nurses working in environments with care limitations.Results70% of respondents reported that they would speak up if they were aware of a situation that was ethically challenging. Respondents reported that it was fairly easy or very easy to defend their values when addressing ancillary staff, coworkers, authorities outside the organization, patients, and patient families. Respondents reported challenges in defending their professional values to charge nurses, physicians, or administrators. In response to a serious ethical problem, 65.8% of respondents answered that they would bring up the problem for discussion, 21.1% would file an internal report, and 13.2% would report externally. Interview participants reported significant social and professional barriers to acting in response to an ethical violation. Willingness to act centered on personal values and not professional codes of ethics.ConclusionsWhile emergency nurses in this study reported high perceived levels of moral courage, they also reported low willingness to act directly, citing burnout and significant social and professional barriers. Adherence to professional codes of ethics is not the primary driver of moral courage.